Classroom Assessment Practices of EFL Lecturers with Current Curriculum Implementation: Where Policy Meets Practice - Alfian, Alfian; Rasyid, M. Nur Akbar; Habibi, Akhmad; Noprival, Noprival; Yusuf, Mohammad (REiLA : Journal of Research and Innovation in Language, 2022)
Within the context of Indonesian higher education, the assessment focuses on the three domains of students’ competencies, namely knowledge, skills, and attitude. Therefore, this study aims to explore the assessment practice of EFL lecturers, especially the methods used in assessing the three students’ competencies. It also explores the general assessment practice and examines differences by educational degree and length of teaching experience. This quantitative study relies on survey data from 71 participants joining the EFL lecturers’ association in Indonesia. Furthermore, the convenient sampling technique was used to determine the sample, and the data were analyzed using SPSS version 24. The results showed that the lecturers employed various methods in assessing the three domains of students’ competencies. It was also found that the lecturers mostly employed observation (66.2%) for assessing attitudes domain, tests (33.8%) for assessing knowledge, and work performance (29.6%) for skills. The findings demonstrated that the lecturers have followed the assessment policy of the government related to the method, purpose, instrumentation, procedure, and reporting grade. The results also showed no differences in the assessment practice between lecturers with Master and Doctoral degrees. Additionally, there was no difference among the four categories of teaching experiences in the assessment practice. These findings are expected to become a reference for lecturers and curriculum development in conducting and designing appropriate assessments to guarantee teaching and learning quality.